2012
DOI: 10.1007/978-3-642-34327-8_17
|View full text |Cite
|
Sign up to set email alerts
|

A Java vs. C++ Performance Evaluation: A 3D Modeling Benchmark

Abstract: Along the years robotics software and applications have been typically implemented in compiled languages, such as C and C++, rather than interpreted languages, like Java. This choice has been due to their well-known faster behaviors, which meet the high performance requirements of robotics. Nevertheless, several projects that implement robotics functionality in Java can be found in literature and different experiments conduced by computer scientists have proved that the difference between Java and C++ is not s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 7 publications
1
7
0
2
Order By: Relevance
“…al. [29] analysed the runtime performance of Java and C++ in the implementation of robotics algorithms. The study reported that on Windows platform, Java is around 1.09 to 1.51 times slower than C++ and around 1.21 to 1.91 times slower on Linux platform.…”
Section: Related Workmentioning
confidence: 99%
“…al. [29] analysed the runtime performance of Java and C++ in the implementation of robotics algorithms. The study reported that on Windows platform, Java is around 1.09 to 1.51 times slower than C++ and around 1.21 to 1.91 times slower on Linux platform.…”
Section: Related Workmentioning
confidence: 99%
“…However, we believe extensive comparisons between the performance of model transformation languages and general-purpose programming languages to be necessary to abolish the prejudice that dedicated transformation languages cannot outperform current compilers. Comparison of performance between different programming languages that are used for the same purpose is a wellestablished practice demonstrated by comparisons between Java and C++ for robotics programming done by Gherardi, Brugali and Comotti [27] or C++ and F90 for scientific programming by Cary et al [18]. Performance comparisons are also common practice in other domains such as GPU programming where specialized DSLs are used and performance is of high importance (Karimi et al [24]).…”
Section: Research Directionmentioning
confidence: 99%
“…Most existing platforms use Java/Groovy as the main language. Despite boasting good multi-platform support and being a modern object-oriented language, the performance of Java compared to C and C++ is debated [11], [12]. It is possible to deploy TensorFlow-based models in Java, with libraries like DeepLearning4J [13], but its support for layers and network architectures is currently limited.…”
Section: Introductionmentioning
confidence: 99%